IN VITRO CYTOTOXICITY ACTIVITY OF METHANOLIC LEAF AND FRUIT EXTRACT OF ZANTHOXYLUM OVALIFOLIUM WIGHT AGAINST DALTON’S LYMPHOMA ASCITES AND EHRLICH ASCITES CARCINOMA CANCER CELL LINES - PAVANI P; RAJA NAIKA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objective of the present study, the methanolic leaf and fruit extraction of Zanthoxylum ovalifolium, was examined for in vitro cytotoxicity using trypan blue dye exclusion technique. Methodology: In vitro cytotoxicity activity of methanolic leaf and fruit extracts of Z. ovalifolium. Against Dalton’s lymphoma ascites (DLA) and Ehrlich ascites carcinoma (EAC) cell lines evaluated using trypan blue exclusion method. Non-viable cell absorbs blue color of trypan blue while viable cell does not absorb the dye. The percentage of total number of viable and non-viable cells is calculated using % viability=(live cell count/total cell count)×100. Results: Cytotoxicity activity of methanolic leaf and fruit extract against chosen tumor cell line at different concentrations of 10, 20, 50,100, and 200 μg/ml, respectively. The result confirmed that the fruit extract at 200 showed less toxic effect against DLA and EAC cell line showed 72% and 75% of inhibition growth of cell line and the most potent 80% and 82% of cell death were found in leaf extract against the chosen tumor cell line. The present study indicates that both leaf and fruit extract of Z. ovalifolium were appreciable antitumor activity against DLA and EAC cell lines may be due to the presence of phytochemicals such as flavonoids and alkaloids present in the plant. Conclusion: Zanthoxylum ovalifolium wight fruit and leaf methanolic extracts showed satisfying result of cytotoxicity activity against DLA and EAC cell line. Hence, Z.ovalifolium could be suggested as an important source of anticancer agent for pharmacological industries.